2016
DOI: 10.1245/s10434-016-5451-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Rectal Cancer With Clinically (EUS/MRI) Metastatic Mesorectal Lymph Nodes Treated by Neoadjuvant Chemoradiation: Role of Organ Preservation Strategies in Relation to Pathologic Response

Abstract: BackgroundOrgan preservation strategies are under investigation for patients with locally advanced rectal cancer (LARC) who achieve a complete pathologic response in the primary tumor (ypT0) after neoadjuvant chemoradiation therapy (CRT). This study explored the value of this approach for cN+ patients.MethodsData were retrieved from our institutional prospective rectal cancer database. Tumors with mesorectal lymph nodes larger than 5 mm shown on endorectal ultrasonography, pelvic magnetic resonance imaging, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…The present study showed that the accuracy rates of ERUS and MRI for detecting metastatic lymph nodes were 44.4% and 66.7%, respectively, which is consistent with previous findings. 6,10 Belluco et al 11 found that in 42.2% of patients who underwent surgery after nCRT treatment found pathological metastatic lymph nodes. However, 16% of surgical specimens existed in the subgroup of patients with YPT0.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the accuracy rates of ERUS and MRI for detecting metastatic lymph nodes were 44.4% and 66.7%, respectively, which is consistent with previous findings. 6,10 Belluco et al 11 found that in 42.2% of patients who underwent surgery after nCRT treatment found pathological metastatic lymph nodes. However, 16% of surgical specimens existed in the subgroup of patients with YPT0.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have evaluated the diagnostic yield of cross-sectional and functional nuclear imaging modalities, data on the role of EUS in rectal cancer follow-up are still lacking. With its tissue acquisition capability, EUS could be a reliable complementary technique in differentiating benign postoperative flogistic tissue from malignant local recurrence [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the included studies are shown in (Tables 1 and 2). Of all 13 studies, ten were CSs (including six propensity score matching analyses) [28][29][30][31][32][33][34][35][36][37], three were RCTs [38][39][40], ten CSs and three RCTs reported LR, four CSs reported LRFS, six CSs and two RCTs reported OS, six CSs and three RCTs reported DFS, two RCTs reported DSS. This study included 1402patients, of which 570 patients (40.66%) underwent TLE and 832 patients (59.34%) underwent TME.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All 10 CSs had a score of �7, indicating a low risk of bias. Among them, 9 CSs [28][29][30][32][33][34][35][36][37] were rated as having incomplete follow-up due to their failure to describe the attrition rate, while 3 studies [31,33,35] were…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%